2014
DOI: 10.5414/cp202117
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of empagliflozin, a sodium glucose cotransporter 2 inhibitor, and simvastatin following co-administration in healthy volunteers

Abstract: No relevant drug-drug interaction was observed, and pharmacokinetic results suggest that no dose adjustments for either drug are necessary when empagliflozin and simvastatin are co-administered. Empagliflozin was well tolerated when administered alone or in combination with simvastatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 0 publications
0
6
0
2
Order By: Relevance
“…29 Dapagliflozin is also metabolized mainly in the liver and kidneys by UGT1A9, 28 and a lack of clinically meaningful DDI was reported when dapagliflozin was coadministered with either sitagliptin, metformin, glimepiride, or simvastatin. 26,27 Similarly, no relevant DDIs were observed when empagliflozin was coadministered with simvastatin, 30 metformin, 31 or sitagliptin. 32 In summary, the lack of PK interactions demonstrates that ertugliflozin can be administered with sitagliptin, metformin, simvastatin, or glimepiride without any need for dose adjustments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Dapagliflozin is also metabolized mainly in the liver and kidneys by UGT1A9, 28 and a lack of clinically meaningful DDI was reported when dapagliflozin was coadministered with either sitagliptin, metformin, glimepiride, or simvastatin. 26,27 Similarly, no relevant DDIs were observed when empagliflozin was coadministered with simvastatin, 30 metformin, 31 or sitagliptin. 32 In summary, the lack of PK interactions demonstrates that ertugliflozin can be administered with sitagliptin, metformin, simvastatin, or glimepiride without any need for dose adjustments.…”
Section: Discussionmentioning
confidence: 99%
“…Dapagliflozin is also metabolized mainly in the liver and kidneys by UGT1A9, and a lack of clinically meaningful DDI was reported when dapagliflozin was coadministered with either sitagliptin, metformin, glimepiride, or simvastatin . Similarly, no relevant DDIs were observed when empagliflozin was coadministered with simvastatin, metformin, or sitagliptin …”
Section: Discussionmentioning
confidence: 99%
“…A series of randomized, open-label, crossover studies in healthy volunteers indicated that there were no clinically relevant interactions between empagliflozin and medications that are commonly prescribed for patients with diabetes (verapamil, ramipril, digoxin, warfarin, gemfibrozil, and simvastatin), nor commonly used contraceptives, 20 and that food had no clinically relevant effect on exposure to empagliflozin. 21-25 A single-dose study in patients with mild, moderate, or severe hepatic impairment demonstrated that no dose adjustment was needed in these groups. 26…”
Section: Empagliflozinmentioning
confidence: 99%
“…Empagliflozina no tuvo efectos en el AUC de simvastatina ácida, su metabolito activo. Los autores concluyeron que no existen interacciones relevantes entre ambas drogas y que no se requiere ajuste en la dosis de estos fármacos al ser co-administrados 22 . Agonistas del receptor del péptido simil glucagón tipo 1 (aGLP-1) Liraglutide, como otros agonistas GLP-1, retrasa el vaciado gástrico.…”
Section: Inhibidores Del Cotransportador Sodio Glucosa Tipo 2 (Isglt-2)unclassified
“…Con respecto a exenatide, esta droga ha sido estudiada con lovastatina en sujetos sanos. No se han detectado cambios significativos y no se recomienda ajuste de dosis en estas combinaciones [18][19][20][21][22][23][24] .…”
Section: Inhibidores De Isglt-2 Y Estatinasunclassified